X≤7
x>3
As a result, the answer will be
3 less than x and less than or equal 7. Hope it help!
We can set Maggie's age to x
If her brother is six years younger than four times her age, than her brother must be equal to: 4x-6
Since the sum of their ages is 39, we can set up an equation.
(Sum of Maggie's age) + (sum of Maggie's brother's age) = 39
x + (4x -6) = 39
5x -6 = 39
5x = 45
x = 9 , Maggie's age is 9
Answer:
1. 2(k + 3)
2. 3. 75 + k
Step-by-step explanation:
1. 2x + 6
Since, 2 is a common factor of 2 and 6, we can take that common outside.
So, 2x + 6 = 2(x + 3)
Note that in the initial expression, this 2 was distributed to arrive at 2x + 6.
2. (1.5 + k) + 2.25
This is simple addition. We can simply remove the brackets to have:
1.5 + k + 2.25
Since, the like terms can be added, we will have:
1.5 + 2. 25 + k
= 3. 75 + k
Answer:
1012
Step-by-step explanation:
She eats 1012 because:
If she eats 45 in 2 minutes then she eats 22.5 in 1 minute.
This is because 45 ÷ 2 = 22.5
Sarah eats blueberries for 45 minutes so we multiply 22.5 by 45
22.5 × 45 = 1012.5
She ate 1012 full berries.
ok so take 4:20 pm and subtract 4 hrs from it so they left at 12: 20 pm
hope this helps :)